Learning Happens: Incorporating a Rhizomatic Perspective into Teaching and Learning - Michael Dillon (Adult Education Research Conference, 2016)
This session will review a rhizomatic perspective of teaching and learning. Data from research regarding a community leadership program will be utilized as an example of applying this perspective.
Keywords: Rhizomatic Learning; Learning Theory; Post-Modern